CRIMINAL LAW ENFORCEMENT AGAINST DOCTORS IN THE APPLICATION OF ARTICLE 308 OF THE HEALTH LAW - Ricky (Proceeding International Conference on Social Sciences, 2026)
Medical healthcare services are tasks performed based on scientific knowledge and competencies acquired through formal, tiered education. Their goal is to restore and protect the health of the community, specifically patients within the scope of healthcare provision. A doctor's criminal liability arises when there is a medical malpractice, which involves errors in diagnosing and providing medical treatment. Patients who suffer harm may seek criminal accountability from doctors. The process of enforcing criminal law against doctors requires recommendations from the Professional Discipline Council to initiate an investigation by law enforcement officers. This, in turn, limits the authority of the police in conducting investigations in accordance with the Criminal Procedure Code (KUHAP). This study adopts a normative legal research method. Normative legal research is a type of legal study based on literature review, examining legal issues through an analysis of laws, including Law No. 17 of 2023, Law No. 8 of 1981, and other references related to the enforcement of criminal law against doctors under Article 308 of the Health Law. The findings of this research are as follows: First, the recommendation from the Professional Discipline Council may obstruct victims from accessing legal protection from law enforcement authorities, as the council only evaluates the application of medical discipline, not the role of law enforcement. Second, the Professional Discipline Council serves merely as an advisory body to law enforcement officers, as it is not a law enforcement agency and lacks the capacity to assess whether there is a legal error in healthcare services.